Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1021/bi015719d
|View full text |Cite
|
Sign up to set email alerts
|

Flavin Recognition by an RNA Aptamer Targeted toward FAD

Abstract: Flavin adenine dinucleotide (FAD) is one of the primary cofactors in biological redox reactions. Designing cofactor-dependent redox ribozymes could benefit from studies of new RNA-cofactor complexes, as would our understanding of ribozyme evolution during an RNA World. We have therefore used the SELEX method to identify RNA aptamers that recognize FAD. Functional analysis of mutant aptamers, S1 nuclease probing, and comparative sequence analysis identified a simple, 45 nt helical structure with several interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…It has been shown that artificial RNA sequences (aptamers) can bind FMN with very high affinity. 44,45 It has also been shown that the regulation of the riboflavin biosynthesis operon in Bacillaceae is based on the interaction of FMN with the mRNA specified by the rib operon resulting in premature transcription termination. 46 A hypothetical RNA world would most probably have required catalytic redox processes, and flavin derivatives would have been excellent candidates due to the fact that the isoalloxazine chromophore can arise by a highly unusual reaction in the absence of any catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that artificial RNA sequences (aptamers) can bind FMN with very high affinity. 44,45 It has also been shown that the regulation of the riboflavin biosynthesis operon in Bacillaceae is based on the interaction of FMN with the mRNA specified by the rib operon resulting in premature transcription termination. 46 A hypothetical RNA world would most probably have required catalytic redox processes, and flavin derivatives would have been excellent candidates due to the fact that the isoalloxazine chromophore can arise by a highly unusual reaction in the absence of any catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-FMN and anti-FAD aptamers were first isolated by Burgstaller and Famulok [63], while Lauhon and Szostak later isolated additional flavin-binding aptamers [70]. An additional class of anti-FAD aptamers was isolated by Burke and co-workers [71]. These aptamers all recognize riboflavin with K d values ranging from 0.5 to 50 mm but have different sequences, and adopt different secondary and tertiary structures: the anti-FMN and anti-FAD binding aptamers found by Burgstaller and Famulok have simple loop structures, the anti-riboflavin aptamers isolated by Lauhon and Szostak fold into intramolecular G-quartets, and the anti-FAD aptamer isolated by Burke and coworkers contains three helices interrupted by several internal bulges.…”
mentioning
confidence: 99%
“…Furthermore the aptamers from the NaCl selection also weakly bound adenosylcobalamin. Roychowdhury-Saha et al (2002) isolated flavin-binding RNA aptamers in a selection targeting FAD. The approximate K d for FAD was 50 mmol/L.…”
Section: Aptamers To Cofactorsmentioning
confidence: 99%